THE ACT OF KILLING A MUGGER IN SELF-DEFENSE: A PERSPECTIVE FROM ISLAMIC CRIMINAL LAW AND THE INDONESIAN PENAL CODE - Sirait, Riziq Rabbani Iwanka; Marpaung, Aripin (Program Studi Sosiologi Universitas Malikussaleh, 2025)
This study aims to explore the legal perspective on killing a robber in self-defense according to Islamic Criminal Law (Fiqh Jinayah) and Indonesian Positive Law. The method used is library research. The findings indicate that many people still lack a clear understanding of the legal provisions regarding killing a robber in self-defense. Meanwhile, cases of robbery targeting personal belongings such as motorcycles, bicycles, and other valuables continue to occur frequently in various regions. This lack of understanding leads to uncertainty when facing such threats, even in situations where the victim may lose their life. In Islamic Criminal Law, self-defense resulting in the death of an attacker can be justified if certain conditions are met, such as a real threat to life or honor. In Indonesian Positive Law, self-defense is regulated in the Criminal Code (KUHP), which provides legal protection to victims who defend themselves proportionally. This study emphasizes the importance of legal education for the public so that individuals understand their rights and limitations when acting in self-defense against criminal acts like robbery.